Global anti-base erosion (GloBE) Rules: Expected implications on multinational entities’ effective tax rate in Malaysia - Foziah, Ramli (2022)
This study was carried out to identify expected implications on multinational entities (MNEs)’ effective tax rate (ETR) in Malaysia from the implementation of Global Anti-Base Erosion (GloBE) Rules under Pillar Two. The level of ETR of MNEs in Malaysia for a period of five years from 2016 to 2020 has been calculated and compared with the Statutory Tax Rate (STR) of 24% and then further compared with the Global Minimum Tax (GMT) rate of 15%, as stipulated in GloBE Rules under Pillar Two. Several interview sessions were also conducted with IRBM staff in order to get their initial insight on the Globe Rules under Pillar Two which will be implemented in Malaysia. The results of the ETR calculation show a low rate compared to the STR of 24% and are found to be in line with the findings of previous studies, giving an indication of the existence of tax planning activities by MNEs in Malaysia. However, the calculated ETR shows a higher percentage compared to the GMT rate of 15% and therefore indicates that in such of scenario, MNEs in Malaysia which are included in the scope of GloBE Rules under Pillar Two are not liable to pay top-up tax. This study applies institutional theory and describes Malaysia's decision along with other countries to join the IF and participate in the implementation of BEPS. Although the ETR calculation results in this study are only a simulation and less accurate due to limited access to MNEs’ data in Malaysia, at least it provides information on the expected implications of implementation of GloBE Rules under Pillar Two in Malaysia